Petroleum System Analysis and Migration Pathways in the Late Paleozoic Source Rock Strata and Sandstone Reservoirs in the Ordos Basin - Qingfeng Guan; Jingong Zhang (Energies)
The migration system, as the primary medium linking source rocks and traps, plays a vital role in studying hydrocarbon migration, accumulation, and reservoir formation. This study focuses on Late Paleozoic source rock (mudstone and coal rock) and sandstone samples from the Ordos Basin. By analyzing permeability, porosity, and their ratios under various conditions, this study evaluates the quality of hydrocarbon migration pathways across different lithologic strata, identifies optimal migration routes, and offers new insights for identifying favorable hydrocarbon exploration areas in the Late Paleozoic of the Ordos Basin. The findings indicate that the permeability ratio between parallel and vertical bedding planes in source rock and sandstone samples ranges from 1 to 4. Post-fracturing, permeability increases by over twofold. On average, sandstone permeability is approximately 0.1 × 10⁻3 μm2, while source rock permeability is about 0.03 × 10⁻3 μm2. Key conclusions include that without fracture development, permeability, and porosity parallel to bedding planes outperform those perpendicular to bedding planes, with sandstone showing better properties than source rocks. When fractures are present, permeability and porosity along the fracture direction are highest, followed by sandstone, with source rocks showing the lowest values. These results advance the theoretical understanding of hydrocarbon migration systems and provide significant guidance for hydrocarbon reservoir exploration and development.